Familial language network vulnerability in primary progressive aphasia. (18th August 2020) - Weintraub, Sandra; Rader, Benjamin; Coventry, Christina; Sridhar, Jaiashre; Wood, Jessica; Guillaume, Kyla A.; Coppola, Giovanni; Ramos, Eliana Marisa; Bonakdarpour, Borna; Rogalski, Emily J.; Mesulam, M. Marsel
Abstract : Objective: To investigate evidence of the potential role of early cortical vulnerability in the development of primary progressive aphasia (PPA). Method: A woman with a diagnosis of PPA and her 9 adult siblings, 7 with developmental language disabilities, underwent neuropsychological testing, structural MRI, and resting-state fMRI. Whole-exome sequencing was conducted for genes associated with dyslexia or with neurodegenerative dementia. Results: The siblings demonstrated lower verbal than nonverbal cognitive test scores in a developmental dyslexia pattern. On structural MRI, although the siblings did not differ from controls in total brain volume, the left hemisphere language area volume was significantly smaller than the right. Furthermore, cortical connectivity between the left superior temporal area, previously identified as the region of peak atrophy in the proband early in the course of illness, and adjacent language network components, including the planum temporale, was decreased in the siblings. No distinctive genetic signatures were identified. Conclusion: This report further supports the hypothesis that at least some cases of PPA may be based on a familial language network vulnerability that interferes with the acquisition of language in some members and that makes the language network a locus of least resistance to the effects of an independently late-arising neurodegenerative disease in others. This association offers a conceptual model to explain why identical neurodegenerative diseases may selectively target the language network in some individuals while targeting networks that regulate memory or behavior in others. The genetic basis for this vulnerability remains to be determined.